The Influence of Entrepreneurial Leadership on Innovativeness Mediated by Digital Leadership - Hidayat, Muhamad (Bandung: Prodi Manajemen FE Universitas Langlangbuana, 2024)
Companies that are affiliated with and part of state companies, such as Krakatau Information Technology, play a greater role in supporting state finances, so their performance needs to be given attention. Efforts to realize this can be made by creating a climate of innovativeness that has implications for positive changes in employees, which can be done through leadership roles with entrepreneurial and digital characteristics, so the aim of this research is to test the construct of the relationship between these variables. Quantitative methods in the space of causality were used in this research by testing PCA data for the validity approach and Cronbach's alpha for measuring reliability, while testing the mediation model using the t-test and Sobel test. The general picture shows that entrepreneurial and digital leadership directly have a positive influence on stimulating employee innovativeness, and the leader's ability to use digital technology is able to positively mediate the influence of entrepreneurial leadership on the innovative behavior of Krakatau I.T. employees.